2018
DOI: 10.1016/j.omtn.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy for Neuropathic Pain through siRNA-IRF5 Gene Delivery with Homing Peptides to Microglia

Abstract: Astrocyte- and microglia-targeting peptides were identified and isolated using phage display technology. A series of procedures, including three cycles of both in vivo and in vitro biopanning, was performed separately in astrocytes and in M1 or M2 microglia, yielding 50–58 phage plaques in each cell type. Analyses of the sequences of this collection identified one candidate homing peptide targeting astrocytes (AS1[C-LNSSQPS-C]) and two candidate homing peptides targeting microglia (MG1[C-HHSSSAR-C] and MG2[C-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 67 publications
(83 reference statements)
0
33
0
Order By: Relevance
“…After decapitation of six C57BL/6 pups 1–2 days postpartum at the same time, mixed glial cells from brain cortex were dissociated, and primary mixed glial cell-culture was established ( Fig. 1 ) [ 24 , 25 ]. After incubation of these mixed glial cells with Dulbecco's Modified Eagle Medium (DMEM)/F12 with 10% FBS (foetal bovine serum) for 14 days at 37 °C, many number of microglia were appeared on layered astrocytes, were isolated by mechanical tapping and transferred to another culture dish.…”
Section: Methodsmentioning
confidence: 99%
“…After decapitation of six C57BL/6 pups 1–2 days postpartum at the same time, mixed glial cells from brain cortex were dissociated, and primary mixed glial cell-culture was established ( Fig. 1 ) [ 24 , 25 ]. After incubation of these mixed glial cells with Dulbecco's Modified Eagle Medium (DMEM)/F12 with 10% FBS (foetal bovine serum) for 14 days at 37 °C, many number of microglia were appeared on layered astrocytes, were isolated by mechanical tapping and transferred to another culture dish.…”
Section: Methodsmentioning
confidence: 99%
“…35 In previous reports, we demonstrated DRG-targeting gene therapy or microglia-specific gene delivery in the spinal cord by intrathecal injection. 6,10 Lumbar puncture and intrathecal injection are usually performed clinically. Side effects include headache and intra- cranial hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…6 In another study, homing peptides to microglia and astrocytes were also identified and applied for the delivery of small interfering RNA (siRNA) to treat neuropathic pain in a mouse model. 10 Although homing peptides have great potential applicability and could become powerful tools for drug and gene delivery, these experiments showed successful results of gene therapy only by the intrathecal route of administration. 6,10 Intrathecal injection after lumbar puncture is routinely performed clinically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, novel microglial targets have been identified. Homing peptides directed towards microglia that contained siRNA for IRF5 resulted in a decrease in neuropathic pain (Terashima et al, ). Injection of microglial precursor cells transduced with TREM2 ex vivo in an EAE model of multiple sclerosis facilitated the clearance of cellular debris and ameliorated the disease (Takahashi et al, ).…”
Section: Targeting Microgliamentioning
confidence: 99%